GLOBAL CONSULTATION ON ESTABLISHMENT A UNIFIED SURVEILLANCE SYSTEM FOR DONATION AND TRANSPLANTATION OF ORGANS, TISSUES AND CELLS OF HUMAN ORIGIN - O. V. Orlova (Вестник трансплантологии и искусственных органов)
From from February 7th to 9th 2011, the World Health Organization (WHO), the Italian National Transplant Cen- tre and the EU-funded Project «Vigilance and Surveillance of Substances of Human Origin» joined forces to organise a major global consultation that took place in Bologna, Italy. The scope of the project included organs, tissues and cells for transplantation and for assisted reproduction. The participants represented regulatory and non-regulatory government agencies, professional societies and scientific and clinical specialities from all WHO regions. The meeting explored the work already carried out on-line and agreed on priorities for the future deve- lopment of the Project «Vigilance and Surveillance of Substances of Human Origin».